2020
DOI: 10.2147/ndt.s252933
|View full text |Cite
|
Sign up to set email alerts
|

<p>Change in Functional Brain Activation Patterns Induced by Olfactory Stimulation in Multiple Sclerosis</p>

Abstract: Background: Olfactory disorder is one of the commonly appearing symptoms in diseases like Parkinson's disease (PD) and Alzheimer's disease (AD). However, reports of olfactory changes in multiple sclerosis (MS) are scarce and usually ignored or seldom recognized by clinicians. The majority of current research is based on subjective answers obtained by smelling odorants. Objective: To gain better insights into the central brain regions involved in the olfactory process. We measured preliminary contrast assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…While the activation of cerebral regions in patients with MS, in regions such as the right insular, bilateral hippocampus, and right parahippocampal gyrus, was different from that in healthy adults. OuYang et al (2020) confirmed olfactory-related changes in cerebral networks of patients with MS. Using fMRI imaging, we observed changes in olfactory-related brain regions and differences in the activation of olfactory-related brain regions in NMOSD and MS patients, it suggests that the pathological changes of the two diseases may involve olfactory disorders caused by olfactory networks, but there are different olfactory-related brain networks between the two diseases.…”
Section: Discussionsupporting
confidence: 58%
“…While the activation of cerebral regions in patients with MS, in regions such as the right insular, bilateral hippocampus, and right parahippocampal gyrus, was different from that in healthy adults. OuYang et al (2020) confirmed olfactory-related changes in cerebral networks of patients with MS. Using fMRI imaging, we observed changes in olfactory-related brain regions and differences in the activation of olfactory-related brain regions in NMOSD and MS patients, it suggests that the pathological changes of the two diseases may involve olfactory disorders caused by olfactory networks, but there are different olfactory-related brain networks between the two diseases.…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, the control group represents healthy individuals without any neurologic disorders and/or diseases. The full list of the included studies is available in the reference section [ 1 , 3 , 6 8 , 13 , 14 , 16 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Olfaction is shown to be prone to impairment in three main aspects, including threshold, discrimination, and identification. Olfactory dysfunctions are reported as one the most common manifestations in the initial stages of certain CNS diseases, including Alzheimer’s disease and Parkinson’s disease [ 6 ]. Moreover, numerous studies have pointed out the presumable connection between olfactory disturbances and not only neurodegenerative diseases but also autoimmune ones, such as (MS) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies also lack coherence regarding the prevalence they report, with numbers ranging from 20% to 40%. (8,9) It is crucial to study olfactory dysfunction as it plays a major role in diminishing one's quality of life,(10) and also because there is growing evidence that the degree to which MS patients present with olfactory problems can be used as a potential prognostic factor. (11) On the other hand, the prevalence of olfactory disturbance among MS patients has been reported in various studies, among different sample sizes with different MS subtypes.…”
Section: Introductionmentioning
confidence: 99%